MAUT method – one in a multiple criteria decision-making methods - Simanavičienė, Rūta (Lietuvos matematikos rinkinys, 2023)
Multiple criteria decision-making methods enable to choose the optimal decision, if his criterions is contradictorys. In herein paper is describe MAUT – multiattribute utility theory. This method is reasoned in theory. MAUT up for indeterminations situations, but can to use for determinations situations. In this method multiple criteria problem solvable with the help of unitary utility functions.